Evaluation of fungal adherence to plasma-modified polymethylmethacrylate - Zamperini, C. A. [UNESP]; Machado, Ana Lucia [UNESP]; Vergani, Carlos Eduardo [UNESP]; Pavarina, Ana Claudia [UNESP]; Rangel, E. C. [UNESP]; Cruz, N. C. [UNESP] (Wiley-Blackwell, 2011)
There is a propensity for fungal adherence to the polymethylmethacrylate used for making denture bases. Therefore, this study investigated whether surface modifications with plasma treatments would reduce the adherence of Candida albicans to a denture base resin. Samples (n = 180) with smooth and rough surfaces were made and divided into five groups: control non-treated; experimental groups submitted to plasma treatments to obtain surfaces with different hydrophobicities (Ar/50 W; ArO(2)/70 W; AAt/130 W) or with incorporated fluoride (Ar/SF(6)70 W). Contact angles were measured immediately after treatments and after samples were immersed in water for 48 h. For each group, half the samples were incubated with saliva before the adherence test. The number of adhered C. albicans was evaluated by counting after crystal violet staining. The plasma treatments were effective in modifying the polymethylmethacrylate surface. However, there was a significant alteration in the contact angle measured after immersion in water. No statistically significant difference in the adherence of C. albicans was observed between the experimental and control groups, irrespective of the presence or absence of saliva, and surface roughness.
Keywords: Candida spp; Candida albicans; fungal adherence; denture stomatitis; cell-surface hydrophobicity